Community Participatory Planning in Development in Lembah Sumara Village, Soyo Jaya District, North Morowali Regency - Nuraisyah, Nuraisyah; Daeng Mamala, Ahmad; Mangngasing, Nasir (Lafadz Jaya Publisher, 2024)
This research is to find out how community participatory planning works in development in Lembah Sumara Village, Soyo Jaya District, North Morowali Regency. The type of research used is descriptive qualitative. Data types use primary data and secondary data. Data collection techniques are carried out through observation, interviews, and documentation. The informant withdrawal technique uses purpose. The data analysis used is the Miles, Huberman, and Saldana model, namely data reduction, data presentation and drawing conclusions. Based on the results of the research conducted, community participatory planning in development in Lembah Sumara Village, Soyo Jaya District, North Morowali Regency still has many problems. When viewed from the planning stages, the dominant ones who appear active during village fund management deliberations are village officials, members of village consultative bodies and community figures who are considered influential. Meanwhile, most of the community does not play an active role at the planning stage because they do not receive invitations during deliberations, so that when decisions are made, they do not represent the aspirations of the community in general. Likewise, public awareness of the development implementation stages is still very low. Indications of this can be seen in the implementation of village fund management policies for development, starting from the planning process to implementing activities which are almost entirely carried out by the village government.